Combined Effect of Message Framing and Endorser Credibility on Buying Interest of Yoghurt Product - Wankar, Tian Jihadhan (2015)
This study aimed to determine the effect of message framing, the credibility of endorser and the combination of message framing with endorser credibility on advertising for consumer buying interest on yoghurt products. This study was an experimental design that involved students as participants. Students were chosen because it they are considered as the yoghurt consumer segment and to facilitate homogenization. While the number of students who participated in this study were 275 people. This research used 11 advertising design as treatment, which consisted of 1) a positive message framing, 2) negative message framing, 3) celebrity endorser, 4) expert endorser, 5) expert celebrity endorser, 6) positive message framing and celebrity endorser, 7 ) positive message framing and expert endorser, 8) message framing and expert celebrity endorser, 9) negative message framing and celebrity endorser, 10) negative message framing and expert endorser, 11) message framing and expert celebrity endorser. This research analysis used paired samples t-test, one way ANOVA and two-ways ANOVA. The results showed that there was a significant difference between the positive message framing and negative message framing on advertising for consumer buying interest in yoghurt. As well as the uses of expert endorser, celebrity endorser and expert celebrity endorser for buying interest of yoghurt. Using of negative message framing and expert endorser in advertising was more effective to create consumers buying interest of the yoghurt products.